Unsymmetrical 1, 1-diborated multisubstituted sp3-carbons formed via a metal-free concerted-asynchronous mechanism1. Issue 37 (7th October 2015) - Cuenca, Ana B.; Cid, Jessica; García-López, Diego; Carbó, Jorge J.; Fernández, Elena
<x xml:space="preserve">Abstract</x> We have experimentally proved and computationally rationalized the unsymmetrical 1, 1-diboration of diazo compounds, formed in situ from aldehydes and cyclic and non-cyclic ketones, in the absence of any transition metal complex.